Efektivitas Penerapan Asas Equality dan Asas Keadilan dalam Pemungutan Pajak Penghasilan Orang Pribadi di Indonesia - Jedyzha Azzariel Priliska; Gunardi Lie (Publikasi Indonesia, 2026)
This study examines the effectiveness of applying the principles of equality and equity in Indonesia's income tax collection system through the self-assessment system supported by DJP's Coretax digital platform. This study aims to investigate the relationship between these two principles in achieving a fair and effective tax system. Using normative methods through a statute approach and a conceptual approach, the study involves data collection and a review of applicable regulations to gain a deep understanding of the effectiveness of applying tax principles. The research stages began with the identification of the main issues, followed by the collection of relevant information, then in-depth analysis, interpretation of results, and the formulation of conclusions. The results of the discussion indicate that the principles of equality and equity are interrelated in ensuring that the tax burden is imposed in accordance with the taxpayer's ability to pay, thereby creating a proportional tax burden. Coretax DJP plays a crucial role in enhancing the system's effectiveness through administrative digitalization, transparency, and more structured oversight. However, there remains potential for discrepancies in data reporting that requires further monitoring.